Pathogenic Effector Th2 Cells in Allergic Eosinophilic Inflammatory Disease - Mitson-Salazar, Alyssa; Prussin, Calman (Frontiers in Medicine, 2017)
There is an absolute requirement for Th2 cells in the pathogenesis of allergen-driven eosinophil-rich type 2 inflammation. Although Th2 cells are generally regarded as a homogeneous population, in the past decade there has been increasing evidence for a minority subpopulation of IL-5+ Th2 cells that have enhanced effector function. This IL-5+ Th2 subpopulation has been termed pathogenic effector Th2 (peTh2), as it exhibits greater effector function and disease association than conventional Th2 cells. peTh2 cells have a different expression profile, differentially express transcription factors, and preferentially use specific signaling pathways. As such, peTh2 cells are a potential target in the treatment of allergic eosinophilic inflammation. This review examines peTh2 cells, both in mouse models and human disease, with an emphasis on their role in the pathogenesis of allergic eosinophilic inflammation.